Kala Sebagai Desain Karakter Buku Interaktif Prokrastinasi Akademik Untuk Mahasiswa 18-25 Tahun : Desain Komunikasi Visual - Fairuz Adilah; Masnuna Masnuna; Sri Wulandari (Pusat Riset dan Inovasi Nasional, 2026)
Academic procrastination is a common behavior among students that can lead to delays in study completion. This study aims to design a character as an educational medium for procrastination through an interactive book tailored to students aged 18–25, using the Research and Development (R&D) method with the ADDIE model and a mixed-method approach. The results show that the designed character is able to represent procrastination behavior both visually and narratively, supported by a semi-realistic illustration style and desaturated colors that reflect a passive psychological condition. The evaluation results indicate positive responses, where the character is considered relatable and helps audiences better understand procrastination behavior. Therefore, character design can serve as a more communicative visual medium compared to text-based media and has the potential to be further developed into digital platforms.